2012
DOI: 10.1105/tpc.111.095174
|View full text |Cite
|
Sign up to set email alerts
|

The Sg-1 Glycosyltransferase Locus Regulates Structural Diversity of Triterpenoid Saponins of Soybean

Abstract: Triterpene saponins are a diverse group of biologically functional products in plants. Saponins usually are glycosylated, which gives rise to a wide diversity of structures and functions. In the group A saponins of soybean (Glycine max), differences in the terminal sugar species located on the C-22 sugar chain of an aglycone core, soyasapogenol A, were observed to be under genetic control. Further genetic analyses and mapping revealed that the structural diversity of glycosylation was determined by multiple al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 87 publications
3
112
0
Order By: Relevance
“…Therefore, our findings indicate that the typical sugar donor specificity of CsGT2 and Sg-1 a for UDP-Xyl results from convergent evolution, because (1) Sg-1 a and CsGT2 are phylogenetically remote GGTs specialized for structurally different substrates (glycosides of large triterpenes versus small volatile monoterpenes, respectively) but with the same sugar donor specificity for UDP-Xyl, and (2) replacement of Ile-141 with a Ser residue in the CsGT2-I141S mutant resulted in a significant decrease in specificity for UDPXyl (Fig. 5C), whereas replacement of Ser-138 with Gly in Sg-1 a (S138G) converted the xylosylating activity into a glucosylating activity (Sayama et al, 2012). These findings not only highlight the plasticity of the sugar donor specificity of UGTs but demonstrate that the metabolic specialization is a consequence of the lineage-specific differentiation of the enzymes.…”
Section: Sugar Donor Specificity Of Csgt2 For Udp-xylmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, our findings indicate that the typical sugar donor specificity of CsGT2 and Sg-1 a for UDP-Xyl results from convergent evolution, because (1) Sg-1 a and CsGT2 are phylogenetically remote GGTs specialized for structurally different substrates (glycosides of large triterpenes versus small volatile monoterpenes, respectively) but with the same sugar donor specificity for UDP-Xyl, and (2) replacement of Ile-141 with a Ser residue in the CsGT2-I141S mutant resulted in a significant decrease in specificity for UDPXyl (Fig. 5C), whereas replacement of Ser-138 with Gly in Sg-1 a (S138G) converted the xylosylating activity into a glucosylating activity (Sayama et al, 2012). These findings not only highlight the plasticity of the sugar donor specificity of UGTs but demonstrate that the metabolic specialization is a consequence of the lineage-specific differentiation of the enzymes.…”
Section: Sugar Donor Specificity Of Csgt2 For Udp-xylmentioning
confidence: 99%
“…These crucial residues for sugar donor specificity are located in three distinguishable regions, the N-terminal, middle, and C-terminal regions (Sayama et al, 2012). Mutagenesis experiments (Ile-141→Ser-141) revealed that the unique Ile-141 of CsGT2 located in the middle region is a residue determining the specificity toward UDP-Xyl.…”
Section: Sugar Donor Specificity Of Csgt2 For Udp-xylmentioning
confidence: 99%
See 2 more Smart Citations
“…4) The Sg-1 locus adds xylose and glucose at the terminal position of the C-22 sugar chain of SS-A by co-dominant alleles Sg-1 a and Sg-1 b , respectively. 21) The Sg-4 locus attaches the second sugar (arabinose) of the C-3 sugar chain of all soyasapogenols. [4][5][6] The Sg-6 locus is assumed to directly and/or indirectly control the presence of SS-H, SS-I, and SS-J.…”
Section: Epistatic Activity Of Soyasaponin Genes Is Specific To Accesmentioning
confidence: 99%